2012
DOI: 10.1097/nmd.0b013e31823e653b
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal Behavior During Clinical Interviews

Abstract: Research has shown that patients with schizophrenia and depression differ from nonclinical subjects in nonverbal behavior. In contrast, there is a paucity of studies addressing differences in nonverbal communication between diagnostic groups and as to what extent nonverbal communication feeds into standard ratings of psychopathology. Twenty-six patients with schizophrenia were compared with 24 patients with affective disorders (13 depressed, 11 manic) regarding their nonverbal behavior using the Ethological Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…The results support past findings on the importance of prosocial and flight behaviours with strengthened methodology [9,11,28]. However, in contrast to some past findings, associations with non-verbal behaviour were only found with negative symptoms and not with other symptom domains.…”
Section: Comparison With the Literaturecontrasting
confidence: 56%
See 3 more Smart Citations
“…The results support past findings on the importance of prosocial and flight behaviours with strengthened methodology [9,11,28]. However, in contrast to some past findings, associations with non-verbal behaviour were only found with negative symptoms and not with other symptom domains.…”
Section: Comparison With the Literaturecontrasting
confidence: 56%
“…Partial correlation analyses and Mann-Whitney U tests were used to assess whether associations could be explained by medication or gender as potential confounders. Antipsychotic medication was adjusted for, similarly to previous analyses [8,31], as medication has been found to correlate with certain non-verbal behaviours in the past [9,32]. Gender was assessed as a possible confounder, as previous studies have found differences in nonverbal behaviour between males and females [2,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic categories may exhibit marked differences in neurodevelopment [3335] but also overlap in terms of shared symptoms: psychotic features are seen in borderline personality disorder [3639], and bipolar disorder and schizophrenia both exhibit similarities in non-verbal communication [40], affective symptoms [41], cognitive deficits [42, 43], genetic risk factors [4446] and a broader trans-diagnostic ‘psychosis’ phenotype [47]. The observation that signs or symptoms are rarely exclusive is an inevitable stumbling block for categorical classification in psychiatry, because they are a distinct manifestation of neurobiological dysfunction whose idiosyncratic expression in an individual patient is shaped by complex environmental factors in the history of that individual’s illness.…”
Section: Step One: Multidimensional Definition Of Disordermentioning
confidence: 99%